Respuesta :

Answer:

–169

Step-by-step explanation:

(f/g)(x) = ( 3 – 2x ) / (1 / x+5)

(f/g)(8) = (3 - 16)/(1/13)

(f/g)(8) = = -13 * 13

(f/g)(8) = - 169

Answer: -169

Step-by-step explanation:

Given functions: [tex]f(x)=3-2x\text{ and } g(x)=\dfrac{1}{x+5}[/tex]

The quotient function (f/g) is given by :_

[tex](f/g)(x)=\dfrac{f(x)}{g(x)}\\\\\Rightarrow (f/g)(x)=\dfrac{3-2x}{\dfrac{1}{x+5}}[/tex]

At x = 8 , we have

[tex](f/g)(8)=\dfrac{3-2(8)}{\dfrac{1}{8+5}}\\\\\Rightarrow\ (f/g)(8)=\dfrac{-13}{\dfrac{1}{13}}\\\\\Rightarrow\ (f/g)(8)=-13\times13=-169[/tex]

Hence, the value of [tex](f/g)(8)=-169[/tex]